PENGUJIAN INVESTMENT RATIO DALAM MENDETEKSI LAPORAN KEUANGAN YANG DIMANIPULASI - Serly; Veronica (Indonesian Journal of Accounting and Governance, 2021)
Financial statements play an important role in providing information about firm performance. Good performance will attract investors and increase investors returns. However, not all companies are able to produce good performance thus encouraging companies to manipulate financial statement. The aim of this research is to detect manipulation in financial statements using investment ratio, such as earning per share, dividend per share, price earning, dividend ratio, total share profitability, and dividend profitability. The indication of manipulation is measured using M-score. As a quantitative study, this study uses secondary data from annual report and financial statements of companies that listed on Indonesia Stock Exchange (IDX). Research shows earning per share and dividend profitability have a significant positive effect on manipulation of financial statement, and dividend per share has a significant negative effect while price/earning, dividend payout ratio, and total share profitability have no significant on manipulation of financial statement.